Rethinking behaviour change interventions in policymaking: comment - Hofmann, Wilhelm; Betsch, Cornelia; Böhm, Robert; de Ridder, Denise; Drews, Stefan; Ewert, Benjamin; Hertwig, Ralph; Sniehotta, Falko F.; Mata, Jutta (Nature human behaviour, 2025)
Behaviour change interventions that are unsuccessful may often be limited by structural constraints. Accumulating evidence across contexts helps to diagnose these barriers. Policymakers should combine structural and behavioural insights to enact systemic reforms to better address environmental and societal challenges.